Penanian Dolo Dalam Tradisi Mabulle Tomate Di Lembang Gandangbatu Sebagai Wujud Akulturasi Budaya - Tandililing, Sostenes Mono; Sunarto, Sunarto; Widodo, Widodo (Visual Heritage: Jurnal Kreasi Seni dan Budaya, 2024)
Penanian Dolo is a song or song that was originally used in the Christian worship procession in Tana Toraja. Penanian Dolo is a spiritual song that was performed by evangelists from the Netherlands in conjunction with the Dutch colonial event in Tana Toraja, this song was then translated into Toraja language and used by Zendeling in the evangelism process. Over time, the Penanian Dolo was used by the Gandangbatu community in the process of carrying the corpse (Ma'bulle To Mate). This study aims to determine the form of Penanian Dolo music and the social values contained in Ma'bulle Tomate activities that have been acculturated with Christian products, namely Penanian Dolo. The research method used in this research is qualitative research using ethnographic and musicological approaches. The results obtained from this study are Penanian Dolo using a simple melody that is easy to memorize and learn by the public. The lyrics of the song Penanian Dolo have a close meaning with an atmosphere of mourning. This tradition has become an icon for the Gandangbatu community, resulting in this activity being preserved until now.